Speech Perception: Phonological Neighborhood Effects on Word Recognition Persist Despite Semantic Sentence Context. Issue 6 (December 2019) - Cervera-Crespo, Teresa; González-Álvarez, Julio
This study tested the hypothesis that two lexical properties, both phonological neighborhood density (ND) and neighborhood frequency (NF), influence the recognition of target words when preceded by either a semantically congruent or semantically neutral context. Our study is the first to test this hypothesis using a language other than English (i.e., Spanish). We used highly familiar bisyllabic nouns with medium-frequency occurrence as target words, and we expected recognition accuracy to increase as ND and NF decreased in both semanticallly congruent and semantically neutral sentences. We presented 48 undergraduate listeners with a set of 80 words, differing in ND and NF, within these two sentence contexts (i.e., 160 sentences). We then tested the relationships between ND, NF, and variations in semantic sentence context within a linear logistic model and found that words with a low frequency of neighbors were more likely to be correctly recognized in both sentence contexts. Thus, during word recognition, the influence of phonological competition outweighed semantic sentence context even when words were presented in Spanish.